THE EFFECTS OF FOOT BINDING CUSTOM IN LISA SEE’S NOVEL SNOW FLOWER AND THE SECRET FAN - Moh. Gusnaldi Putra; M Manugeren (JOURNAL OF LANGUAGE, 2019)
This study constitutes an Analysis of The Effect of Foot Binding Custom from Lisa See’s novel Snow Flower and The Secret Fan published in 2006. The Positive and Negative effects are the topics to discuss. This analysis uses the data  taken from the novel applying descriptive qualitative research. One of the significant theories of the custom used in this study is that a person who claims that the essence of a culture having a custom in it is not its artifacts, tools, or other tangible cultural elements but how the members of the group interpret, use, and perceive them. It is the values, symbols, interpretations, and perspectives that distinguish one from another in modernized societies; it is not material objects and other tangible aspects of human societies. People within a culture usually interpret the meaning of symbols, artifacts, and behaviors in the same or in similar ways. The findings show that Foot Binding Custom gives women positive effects such as high statue in the society, and symbol of beauty. Besides the positive effects, there are also negative effects such as infection, and even death. The conclusions of the study are Foot binding, as the time goes by, is not persevered anymore as it gives more negative effects than the positive ones. However, health is the most important part of human life. Health is the pivot upon which a man's whole personality and its well-being depend. An ailing and aching body saps the enthusiasm for pursuit. Unwholesome feelings and sensations retard the pace of functional activity, economic development and spiritual uplift.